Caracterização socioambiental do Assentamento Rural Horto Vergel (Mogi Mirim-SP) - Esporte, Sérgio Henrique de Campos (2022)
The general objective of this research is to characterize the environmental and social dynamics of the Vergel Rural Settlement. In order to reach this objective, we will also go through some specific objectives: to understand the historical and current aspects in relation to the process of occupation and permanence of the settlers; recognize the settlement's relations with the cities of Mogi Mirim and Itapira (country-city relationship) and highlight the main social and environmental themes that permeate the reality of the settlement. The methodological course of the research consisted of the following steps: survey of reports and news; fieldwork; interpretation of geographic information; and collecting testimonies from residents on issues surrounding the settlement. The results showed that what stands out throughout the history of the settlement is agricultural production, mainly subsistence, and the successive attempts to commercialize its products. On the other hand, non-agricultural productions appear as a complement to the income of the families who live there. In short, we consider the relevance of surveying and relating the elements referring to the environmental and cultural dynamics from the spatialization of elements and phenomena through the collection of quantitative and qualitative data that contribute to the planning of the territory from the apprehension of information by the community and by the public power, in the sense of subsidizing decision-making and alternatives for the management of the territory.